The Effect of Storytelling Technique towards Students' Speaking Ability: At Class XI of State Islamic Senior High School (MAN) Salido - Hairi Yanto (English Education Study Program Faculty of Teacher Training and Education, 2018)
Abstract The main purpose of teaching English is students able to active or passive communicate in English well. This research was experiments research with using a quantitative approach. This research focus on use storytelling techniques on speaking ability, to determine whether storytelling techniques give a significant effect towards students' speaking ability, and to determine components of speaking skill that improved by implementation of storytelling technique on students’ speaking abilities such as vocabulary, pronunciation, grammar, fluency, and understanding. The populations in this research were all students in grade Salido, amounting to 239 people in seven classes spread. Technique of sampling in this researchuster random sampling; where one each class has the same chance to be made as a sample. Then the sample was selected class XI IPK 1 as an experiment classes totaling 30 students and the class XI IPK 2 as a control class with the number of students were 35 students. The experiment class used the storytelling technique one time a week while the control class was not trained on this technique. The instruments in the researchers was used a pre-test and post-test of speak data collections was administered to all subjects for examining their ability in speaking skill. Independent sample t-test and paired t-test were performed for data analysis. The results showed that the story-telling technique gave a significant effect towards students’ speaking ability. And components of speaking skill that can be improved by implementation of story-telling technique on students at class eleven are pronunciations. It can be concluded that the story telling technique is very effective used in speaking of learning and positive implications for increasing students' speaking ability.